2018
DOI: 10.1007/5584_2018_160
|View full text |Cite
|
Sign up to set email alerts
|

COPD Course and Comorbidities: Are There Gender Differences?

Abstract: The prevalence of chronic obstructive pulmonary disease (COPD) has increased more rapidly in women than in men during the past two decades. Clinical presentation, comorbidities and prognosis may differ between genders and may influence management decisions. The influence of gender on COPD expression has not been clearly explained to date. Thus, the aim of this study was to evaluate significant differences between women and men suffering from COPD, regarding clinical presentation, pulmonary function test result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
4
11
1
Order By: Relevance
“…Indeed, we observed a gender divergence in TLC and RV, without any difference in BMI. The increase of TLC and RV %pv observed in women in our study was also found in other recent studies [60][61][62]. These data suggested that, for a given FEV1, women had a more pronounced air trapping or hyperinflation than men, while hyperinflation was quite limited in our study (mean TLC was 105%pv in women and 87%pv in men).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, we observed a gender divergence in TLC and RV, without any difference in BMI. The increase of TLC and RV %pv observed in women in our study was also found in other recent studies [60][61][62]. These data suggested that, for a given FEV1, women had a more pronounced air trapping or hyperinflation than men, while hyperinflation was quite limited in our study (mean TLC was 105%pv in women and 87%pv in men).…”
Section: Discussionsupporting
confidence: 91%
“…These data suggested that, for a given FEV1, women had a more pronounced air trapping or hyperinflation than men, while hyperinflation was quite limited in our study (mean TLC was 105%pv in women and 87%pv in men). These observations are consistent with Grabicki et al that showed that COPD women had more hyperinflation, air trapping and comorbidities, inducing a higher risk of mortality [61]. In addition, in women, this increased air trapping also led to the development of hypercapnia [63].…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has found that there were significant differences between male patients and female patients in terms of disease severity, comorbidities and prognosis. 42,43 Although COPD has always been considered as the disease of elderly men, the burden of COPD on female patients has gradually increased in recent years. We hope that there will be more studies on female COPD patients in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Female patients develop COPD at earlier ages with lower tobacco consumption in comparison to males [4], and their quality of life is more impaired [25]. Females have an increased susceptibility to COPD due to sex-related biological factors [26] and may have different responses to medical treatment, follow-ups, smoking cessation interventions and pulmonary rehabilitation programmes [27][28][29][30][31][32]. Women with COPD exacerbations are younger, smoke more actively and have less comorbidity [33].…”
Section: Discussionmentioning
confidence: 99%